Effect of polymer matrix on photosensitivity of meso-CI polymethine dye based composites - Berezina, N.; Syromyatnikov, V.; Ishchenko, A.; Verbitsky, A.; Vertsimakha, Ya. (Functional Materials, 2006)
Optical and photovoltaic properties of polymer composites with high (40 %) concentration of Cl-containing polymethine dye (meso-CI) films have been studied. As polymer matrix, carbazole containing polymers: poly-N-vinylcarbazole poly-N-epoxypropylcarbazole, octyl methacrylate-N-vinylcarbazole, and octyl methacrylate-3-iodo-N-vinylcarbazole (3I-VCz-OMA) copolymers were used. Several types of aggregates have been shown to be formed in meso-CI/polymer films. This results in significant widening of the absorbance spectral region towards shorter wavelengths (up to 500 nm) as compared to the molecular absorbance in solutions. The charge carrier photogeneration efficiency for aggregates depends heavily on the polymer matrix. The composite on 3I-VCz-OMA base have maximal photosensitivity among the polymer matrices studied. The effect of molecular structure of polymers and dyes as well as the dye aggregation on photovoltaic properties of composite films is discussed. The composite films can be used for the development of plastic photoconverters sensitive in near-IR region, including organic solar cells.